The Effect of Various Seed Coating Materials on the Growth of Soybean (Glycine max L. Merrill) Seeds after 3 Months of Storage - Oki Nur Hidayah; Agus Sulistyono; Ida Retno Moeldjani (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Efforts to improve the quality of the Anjasmoro soybean variety (Glycine max L. Merrill) include the use of seed coating techniques. Seed coating involves applying a layer of specific materials to seeds, serving as carriers for additional substances that extend seed shelf life, protect against pathogens, and stimulate plant growth. This study aimed to identify the most effective seed coating material to enhance soybean growth after storage for three months. Growth tests were conducted using the following treatments: FP 0 (control); FP 1 (CMC 1.5% + Liquid Smoke 0.5% + CaCO₃ 72 g + Gypsum 18 g); FP 2 (CMC 1.5% + Liquid Smoke 0.5% + CaCO₃ 72 g + Talc 18 g); FP 3 (CMC 1.5% + Liquid Smoke 0.5% + CaCO₃ 72 g + Pumice stone 18 g); FP 4 (CMC 1.5% + Liquid Smoke 0.5% + CaCO₃ 72 g + Quicklime 18 g); FP 5 (CMC 1.5% + Liquid Smoke 0.5% + CaCO₃ 72 g + Dolomite 18 g); and FP 6 (CMC 1.5% + Liquid Smoke 0.5% + CaCO₃ 72 g + Zeolite 18 g). Observations included plant height (cm), number of leaves, and number of branches. The study was conducted from April to October 2024 at the UPT Center for Rice and Secondary Crops Seed Development 2, Singosari District, Malang, using a randomized block design (RAK) with seven formulations of seed coating materials. Each treatment consisted of 16 plants with four replications. The research data were analyzed using ANOVA, followed by a BNJ (Honestly Significant Difference) test at the 5% significance level (BNJ 0.05). The results showed that the FP 1 treatment resulted in a plant height of 56.50 cm, 19.75 leaves, and 4.75 branches at 35 days after planting (DAP). The FP 1 treatment significantly enhanced growth, as indicated by plant height, leaf number, and branch number. FP 1 demonstrated the best combination of seed coating materials compared to other treatments at 21, 28, and 35 DAP